Investigating the effectiveness of a study skills training programme - Sikhwari, T.D.; Pillay, J (South African Journal of Higher Education, 2016)
Various studies have shown that the school system in South Africa is continually producing learners who are inadequately prepared for higher education studies, particularly schools in disadvantaged environments. The University of Venda (UNIVEN) is situated in an educationally disadvantaged environment. Most of the students who enroll at this university come from areas characterised by educational backlogs and low socio-economic status, among others.